2020
DOI: 10.31024/apj.2020.5.3.6
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on Citrullus colocynthis seeds for aphrodisiac activity in male albino rats

Abstract: An aphrodisiac is defined as an agent that arouses sexual desire. Many natural substances have historically been known as aphrodisiac (Ang and Sim, 2001). Sexual dysfunction is a repeated inability to achieve normal sexual intercourse, which includes various forms like premature ejaculation, retrograded, or retarded ejaculation, erectile dysfunction, arousal difficulties, etc. Several management options employed are associated with some serious side effects and are not readily available and expensive. The sear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Tribulus terrestris is a botanical species that has a long history of traditional use for various purposes, including addressing sexual impotence, edema, abdominal distention, cardiovascular ailments, renal disorders, and as a medicine for coughs. According to research, Paederia foetida has been found to have potential benefits such as improving sexual potency, increasing semen volume, enhancing physical strength, and promoting a youthful appearance [6]. The aim of this study was to examine the potential aphrodisiac effects of the extract derived from Butea superba Roxb.…”
Section: Introductionmentioning
confidence: 99%
“…Tribulus terrestris is a botanical species that has a long history of traditional use for various purposes, including addressing sexual impotence, edema, abdominal distention, cardiovascular ailments, renal disorders, and as a medicine for coughs. According to research, Paederia foetida has been found to have potential benefits such as improving sexual potency, increasing semen volume, enhancing physical strength, and promoting a youthful appearance [6]. The aim of this study was to examine the potential aphrodisiac effects of the extract derived from Butea superba Roxb.…”
Section: Introductionmentioning
confidence: 99%